Tunable High‐Performance Microwave Absorption of Co1–xS Hollow Spheres Constructed by Nanosheets within Ultralow Filler Loading - Zhang, Xiao‐Juan; Zhu, Jia‐Qiang; Yin, Peng‐Gang; Guo, Ao‐Ping; Huang, An‐Ping; Guo, Lin; Wang, Guang‐Sheng (Advanced functional materials, 2018)
Absorbers with lightweight, low filler loading and broad absorption band are highly desirable for electromagnetic wave absorption field. Here, hollow Co1–xS microspheres constructed by nanosheets are fabricated via a facile synthetic method based on hydrothermal route. As an efficient wave absorber, the Co1–xS hollow spheres demonstrate excellent microwave absorption performance. With a weight content of only 3 wt%, the maximum reflection loss (RL) can reach as strong as −46.1 dB at 13.92 GHz and its qualified frequency bandwidth (with RL value over −10 dB) remarkably achieves 5.6 GHz, covering 35% of the entire measured bandwidth. In addition, compared with other cobalt sulfides (such as CoS2 and Co9S8), the Co1–xS microspheres with hollow structure exhibit more superior absorption intensity and broader qualified bandwidth. Therefore, this work provides a promising approach for the design and synthesis of hollow Co1–xS microspheres with lightweight and high‐performance microwave absorption. The hollow Co1–xS microspheres with understanding microwave absorption performance are successfully fabricated through a facile hydrothermal route. The RLmax can reach to −46.1 dB at 13.92 GHz with an ultralow filler loading (3 wt%) and the effective frequency bandwidth is up to 5.6 GHz. Moreover, the possible wave absorption mechanism is also depicted comprehensively in this article.